Persepsi Siswa terhadap Kurikulum 2013 Mata Pelajaran Seni Budaya Pada Kelas VII.3 di SMP Negeri 13 Pekanbaru Tahun pelajaran 2016/2017 - Husni Sasmita (Instructional Development Journal, 2018)
This study aims to determine and describe student perceptions towards the 2013 curriculum on art and culture subjects (music arts) in Public Middle School 13 Pekanbaru. The perception in question is the response of students to the 2013 curriculum in the eye art and culture lessons (music arts). Based on the results of this study, it can be concluded that students in the State Junior High School 13 Pekanbaru in the 2016/2017 school year have a good perception 2013 curriculum. This is evidenced from 40 respondents, there are 10 students (25%) have a good perception, 18 students (45%) have fairly good perceptions high and there are 9 students (22.5%) who have poor / less high perceptions, 3 students (7.5%) have very poor perceptions.